(untitled) (Eurasian Scientific Herald, 2024)
This article contains comments by the author about the method of formation of econometric competences of students in theoretical and practical classes of econometrics. Also, the three main classes in which econometric models can be used in analysis and forecasting, as well as the stages of the modular teaching system in teaching econometrics are presented.